Analysis of cyclic fatigue resistance of ProTaper Universal and ProTaper Next rotary instruments - Stošić Nenad; Popović Jelena; Anđelković-Apostolović Marija; Mitić Aleksandar; Barac Radomir; Nikolić Marija; Igić Marko (Serbian Medical Society - Dental Section, Belgrade, 2022)
Introduction Root canal preparation is one of the most important active phases in the treatment of infected and noninfected teeth. Nickel-titanium (NiTi) instruments are increasingly used in endodontic therapy due to their superior properties compared to those made of stainless steel. The aim of this research was to perform an analysis and comparison of cyclic fatigue in ProTaper Universal and ProTaper Next rotary NiTi instruments in full rotation in simulated canals. Material and methods Twelve ProTaper Next and twelve ProTaper Universal instruments were analyzed in the study. The instruments were tested in an artificial canal stuffed in a metal block at an angle of 45° and a corner radius of 5 mm. The operating time of each instrument until fracture was measured and the number of cycles to fracture (NCF) calculated. Results ProTaper Next instruments showed greater resistance to cyclic fatigue compared to ProTaper Universal. The NCF value was significantly higher in ProTaper Next (1,296.83±20.2) instruments (p<0.001). The average length of fractured fragments was statistically significantly higher in ProTaper Universal (4.52±0.33) instruments compared to ProTaper Next (3.82±0.27) (p<0.001). Conclusion It was concluded that the cyclic fatigue resistance of ProTaper Next instruments was higher compared to ProTaper Universal instruments.